Revision of the Australian bee fly genus Pilosia Hull, 1973 (Bombyliidae, Bombyliinae) from Western Australia - Li, Xuankun; Yeates, David K. (Zootaxa, 2018)
A restricted Western Australia bee fly genus Pilosia Hull (Bombyliidae, Bombyliinae) is reviewed with the description of two new species, Pilosia incana Bowden & Li sp. nov. and Pilosia flava Li & Yeates sp. nov., and the type species, Pilosia flavopilosa Hull, 1973 is identified as a new junior synonym of Pilosia immutatus (Walker, 1849). This genus can easily be distinguished from other Australian genera in the subfamily by having a three-segmented antennal flagellum, a closed cell cup and a haired mediotergite. A recent morphological phylogeny of Australian Bombyliinae suggested Pilosia is sister to all the remaining Bombyliinae genera (Li & Yeates, 2018). A key to all three known species of Pilosia is provided